When Terms Become Neologisms: A Contribution to the Study of Neology from the Perspective of Determinologisation - Humbert-Droz, Julie (CLINA Revista Interdisciplinaria de Traducción Interpretación y Comunicación Intercultural, 2023)
This paper deals with the issues of determinologisation and neology. Even though many existing studies focus on the description of the many aspects of neology, few studies address the relation between determinologisation and neology. For this reason, this paper proposes a different perspective on neological processes, based on an analysis of terms in a corpus that represents different stages of the determinologisation process in particle physics, in French. First, the main semantic phenomena occurring in the determinologisation process are described; then, the terms that acquire new metaphorical meanings in general press are discussed in more detail. Results show that a finer description of the semantic phenomena at stake can lead to a better understanding of the mechanisms allowing for the creation of neologisms in general language.